AVALIAÇÃO DA GERAÇÃO DE BIOGÁS A PARTIR DA BIODIGESTÃO ANAERÓBIA DA FRAÇÃO ORGÂNICA DE RESÍDUOS SÓLIDOS MUNICIPAIS UTILIZANDO DEJETO ANIMAL SUÍNO E BOVINO - LOS, FABÍOLE JORDANA (2015)
This study aimed to evaluate the effect of using different inoculum of animal waste in different proportions in the determination of biogas generation potential from the organic fraction of urban solid waste. Therefore, two different inoculums (swine and cattle manure) were studied at proportion 1g SV inoculum and 1g SV substrate / 1g SV in order to determine their influence on the generation of biogas and, for bovine manure two distinct proportions (3g SV substrate / 1g SV inoculum and 1g SV substrate/1g SV) were employed in order to evaluate the influence of this parameter in the biogas generation. From the choice of these fractions it was determined the influence of the difference of physicochemical parameters (humidity, SV, ST, COD, P, N, C, C / N, pH and alkalinity) initials and final, at different biogas productions, as well as the different proportions of CH4, CO2 and H2S from the compositions of biogas generated, in mesophilic conditions, with an initial moisture percentage of 85%. Of this way, the method of biochemical potential of methane (BPM) was used to evaluate the potential for biogas generation As a result, it was observed that the average biogas generation attributed to the residue was highly dependent on the type of inoculum that was used, whereas for the suine manure in the proportion of 1gSV residue: 1 gSV manure, the biogas production amounted 60,41 mL.gsv added-1 and for the cattle manure, at the same proportion, the generation of biogas did not exceed 4,77 mL.gsv added-1.. The proportion of substrate inoculum also showed different results, being that the proportion 3: 1 in the bovine manure had a cumulative biogas generation equal to 18.44 and the 1: 1 ratio, less than half of this production was achieved, reaching 4,77 mL.gsv added-1.By linking these differences of biogas generation to initials and final parameters obtained, it is observed that the largest generation of biogas (from swine manure, 1: 1) are those bio-digesters with higher initial and final alkalinity , higher final pH, and the biggest reduction in SV (28.61%) followed by bovine manure digesters in the proportions 3: 1 to 1: 1. The pH is considered as a possibility of the inhibition of the process, due to the low final pH obtained for both bio-digesters, as alkalinity. The final physical-chemical parameters showed a remainder of more than 80% volatile solids remained at the end of digestion, indicating a potential of degradation of the mass present in the bio-digester. In relation of the biogas characterization, there was no significant difference in the concentration of methane present in the biogas generated, over the 50 days of digestion. Thus, it was found that the successful application of anaerobic co-digestion to biogas (methane) depends of the quality and source of the substrate and inoculum employed and the proportion substrate / inoculum applied, which directly influence in the anaerobic digestion process.